Integrative proteomics and metabolomics approach to identify the key roles of icariin-mediated protective effects against cyclophosphamide-induced spermatogenesis dysfunction in mice - Fang, Chunyan; Ye, Yulong; Yang, Fang; Wang, Fangyue; Shen, Yifeng; Chang, Degui; You, Yaodong (Frontiers in Pharmacology, 2022)
The alkylating antineoplastic agent cyclophosphamide (CP) is known to be toxic to the male reproductive system, but there are no effective prevention or treatment options. The flavonoid icariin (ICA), which is used in Chinese medicine, has been shown to have a number of biological functions, including testicular protection. The current study looked into the protective effects of ICA in preventing CP-induced spermatogenesis dysfunction. The current study looked into the role of ICA in preventing testicular dysfunction caused by CP. For 5 days, healthy adult mice were given saline or a single dose of CP (50 mg/kg) intraperitoneally (i.p). For the next 30 days, mice were given ICA (80 mg/kg) by gavage. Animals were euthanized 12 hours after receiving ICA, and testes were removed for biochemical, histopathological, sperm evaluation, and transmission electron microscope analysis (TEM). We also investigated the potential biological effects of ICA on CP-induced spermatogenesis dysfunction in mice using an integrated proteomic and metabolomic approach. The levels of 8309 proteins and 600 metabolites were measured. The majority of the differential proteins and metabolites were found to be enriched in a variety of metabolic pathways, including the PI3K-Akt signaling pathway, necroptosis, the mTOR signaling pathway, glycerophospholipid metabolism, and ABC transporters, implying that ICA may have molecular mechanisms that contribute to CP-induced spermatogenesis dysfunction in the testis. Taken together, these findings show that ICA effectively reduces testis injury, implying that ICA may have a role in male infertility preservation.